Strategi Pembelajaran Masa Depan Dalam Penggunaan Blended Learning di Sekolah Dasar: Strategi Pembelajaran Masa Depan Dalam Penggunaan Blended Learning di Sekolah Dasar - Tri Maya Sari (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to explore the role and application of blended learning strategies in elementary school learning. Blended learning is a combination of various strategies or learning methods used to achieve learning objectives. There are three main components of a blended learning strategy, namely 1) online learning, 2) in-person meetings, and 3) independent learning. This strategy is a suitable combination for the future of learning due to the significant advancement of information and communication technology in Indonesia. The method used in this study uses a literature review approach based on relevant previous research results. The results of the study in this study obtained synthesis that the blanded learning method is a very effective method and is highly recommended to be used in the current learning process.